2012
DOI: 10.1111/j.1365-2559.2011.04155.x
|View full text |Cite
|
Sign up to set email alerts
|

Mucinous differentiation in colorectal cancer – indicator of poor prognosis?

Abstract: Langner C, Harbaum L, Pollheimer M J, Kornprat P, Lindtner R A, Schlemmer A, Vieth M & Rehak P 
(2012) Histopathology 60, 1060–1072 Mucinous differentiation in colorectal cancer – indicator of poor prognosis? Aims:  To analyse the prognostic impact of mucinous differentiation in colorectal mucinous adenocarcinomas and adenocarcinomas with a mucinous component. Methods and results:  A total of 381 tumours were reviewed for mucinous differentiation by two independent pathologists. Mismatch repair status was asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
2
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 48 publications
1
49
2
2
Order By: Relevance
“…Some studies had suggested that MUC had a worse prognosis compared with non-MUC (Kanemitsu et al, 2003;Verhulst et al, 2012;Biffi et al, 2013). Others reported no differences (Leopoldo et al, 2007;Farhat et al, 2008;Xie et al, 2009;Langner et al, 2012;Yamaguchi et al, 2012). In present study, we found patient with MUC had a worse prognosis than non-MUC (both adenocarcinomas containing mucin component and without mucin component) in all patients with stage Ⅲ rectal carcinoma.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…Some studies had suggested that MUC had a worse prognosis compared with non-MUC (Kanemitsu et al, 2003;Verhulst et al, 2012;Biffi et al, 2013). Others reported no differences (Leopoldo et al, 2007;Farhat et al, 2008;Xie et al, 2009;Langner et al, 2012;Yamaguchi et al, 2012). In present study, we found patient with MUC had a worse prognosis than non-MUC (both adenocarcinomas containing mucin component and without mucin component) in all patients with stage Ⅲ rectal carcinoma.…”
Section: Discussionsupporting
confidence: 57%
“…Langner et al suggested that recording of mucinous differentiation should be used as an indicator of mismatch repair deficiency, but not for prognostic stratification (Langner et al, 2012). Patients with stage I-III were included in that study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are 3759 English literatures in original search, after exclusion and screening, 28 English literatures (Cusack et al, 1996;Sun et al, 1996;Wu et al, 1996;Enriquez et al, 1998;Cerottini et al, 1999;Consorti et al, 2000;Nozoe et al, 2000;Kanemitsu et al, 2003;Chen et al, 2004;Du et al, 2004;Papadopoulos et al, 2004;Kang et al, 2005;You et al, 2006;Grillo-Ruggieri et al, 2007;Hill et al, 2007;Lee et al, 2007;Farhat et al, 2008;Pande et al, 2008;Catalano et al, 2009;Min et al, 2009;Song et al, 2009;Xie et al, 2009;Sultan et al, 2010;Catalano et al, 2011;Jivapaisarnpong et al, 2011;Hyngstrom et al, 2012;Langner et al, 2012;Yamaguchi et al, 2012) and 2 Chinese literatures (Songqing et al, 2002;Miao et al, 2005) meet the requirements. In the 30 literatures, 21 literatures can be used for Meta analysis of the relationship of mucinous adenocarcinoma and TNM staging, including 444489 cases, in which mucinous adenocarcinoma were 45050 cases, accounting for 10.1% of all cases; 21 literatures can be used for Meta analysis of relationship of mucinous adenocarcinoma and prognosis, including 450804 cases, in which mucinous adenocarcinoma were 45354 cases, accounting for 10.1% of all cases.…”
Section: The General Results Of Selected Literaturementioning
confidence: 99%